The kings of Rome and the first developments of the Roman Republic according to Eutropius: annotated translation of the first book of his ’Breviarium’ - Sant’Anna, Henrique Modanez de (Romanitas - Revista de Estudos Grecolatinos, 2016)
This paper presents a translation with commentary of the first book of Eutropius’ Breviarium, which was written at some point between 367 and 378 AD. It offers an updated Portuguese version of Eutropius’ text, in particular of the part dedicated both to the Roman monarchical period and the early Roman republic. As one can notice from the contents of this book, Eutropius owns his interpretation to Livy though some information he gives is curiously dissonant.